Influence of Interface Layer on the Properties of Exploding Foil Flyer Generator by Integrating Al/Ni Multilayers. Issue 11 (6th May 2020) - Wang, Yao; Zhou, Qin; Jiang, Hongchuan; Xing, Zongren; Li, Yong; Tang, Duo; Qin, Wenzhi; Wang, Liang; Guo, Fei
Abstract : Reactive multilayer films (RMFs) are a type of a thermite nanoenergetic multilayer film, which can be potentially applied to an exploding foil flyer generator (EFFG). Herein, Al/Ni RMFs with a bilayer thickness of 500 nm are integrated into an exploding foil layer by a magnetron sputtering method. The effects of interface layer on the properties of the EFFG are systematically investigated in terms of the electrical behavior and flyer velocity. The interface layer is controlled by annealing, whose structure and chemical composition are confirmed by X‐ray diffraction and transmission electron microscopy. The periodic multilayer structure can be clearly visible, and the thickness of interface layer increases with increasing annealing temperatures from room temperature to 573 K. The EFFG integrating as‐deposited Al/Ni RMFs exhibits improved exploding properties with a short exploding time, violent explosion region, and high flyer velocity phenomenon in comparison with generator at 573 K. Overall, the EFFGs integrated Al/Ni RMFs with larger interface layers can decrease the electrical plasma performances, which are significant for investigating the applicability in various engineering fields. Abstract : The interface layer of Al/Ni reactive multilayer films (RMFs) is controlled by adjusting annealing temperatures. The effects of interface layer on the properties for an exploding foil flyer generator (EFFG) are systematically investigated by synchronously recording current, voltage, and flyer velocity. The results show that the EFFG integrated Al/Ni RMFs with larger interface layer decreases the electrical plasma performances.